2012
DOI: 10.1080/10486801.2011.645283
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Prehistory of Live Art in the UK

Abstract: Roms, H., Edwards, R. (2012). Towards a Prehistory of Live Art in the UK. Contemporary Theatre Review, 22 (1), 17-31. Special Issue: Live Art in the UK (issue editor: Dominic Johnson)Peer reviewe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although there are many opinions about art, it can be concluded that art is an idea, a thought, a feeling that is manifested or expressed through certain elements, which are beautiful to meet human needs (Dharmawati, 2016;Tatarkiewicz, 1974;Kaye, 1994;Whybrow, 2010;Roms & Edwards, 2012;Lambert, 2018).…”
Section: Students' Art Learning Interestmentioning
confidence: 99%
“…Although there are many opinions about art, it can be concluded that art is an idea, a thought, a feeling that is manifested or expressed through certain elements, which are beautiful to meet human needs (Dharmawati, 2016;Tatarkiewicz, 1974;Kaye, 1994;Whybrow, 2010;Roms & Edwards, 2012;Lambert, 2018).…”
Section: Students' Art Learning Interestmentioning
confidence: 99%